THE IMPORTANCE OF PHILOSOPHICAL THINKING SKILLS IN SCIENTIFIC RESEARCH - Koussa Narimane (International Journal of Innovative Technologies in Social Science, 2025)
Through this research, we seek to raise one of the current issues, which deals with the importance of employing philosophical thinking skills in scientific research. We focus here on the skill of communication, especially since the communicative act in its various forms and perceptions contributes in one way or another to the activation of various research efforts in reality, and is a bridge between the theoretical visions and the applied results of many researches issued by university institutions, especially in the field of humanities and social sciences. With this in mind, we pose the following question: How can philosophical thinking skills contribute to achieving solid research results in various scientific disciplines?